Chemotherapy in geriatric patients with poor performance status small cell lung cancer: Series from a tertiary care center. Issue 2 (16th April 2022) - Sundriyal, Deepak; Kumar, Parmod; Kumar, Ujjawal; Sehrawat, Amit
Abstract : Geriatric age group patients with poor performance status and advanced stage cancer are often denied chemotherapy. In this series of cases, we demonstrated that systemic anti‐cancer therapy can be considered in these patients after a meticulous modification of the chemo‐protocol.